Analysis of inequalities in the appropriate treatment in the Primary Care Units of the State Health Services of Mexico - Díaz de León Castañeda, Christian (Población y Salud en Mesoamérica, 2017)
Objective: To analyze responsiveness inequalities in the care of patients without social security that use outpatient health services in the Primary Care Units (PCU) of the state health services of the Ministry of Health in Mexico.Methods: It is a cross-sectional and ecological design that considers the federative entities of Mexico as units of analysis. Users reported time-out and quality perception data were used from the National Health and Nutrition Survey (ENSANUT). Some Responsiveness Indicators (RI) were proposed, and suggested inequality indicators were calculated. Likewise, proxy Indicators of Social determinants of Health (IPDSS) were collected from the literature to analyze possible association between ITA and IPDSS through correlation and regression analysis (effect index). Results: Inequalities in ITAs were identified among the federative entities of Mexico, mainly in the indicators of waiting time (absolute disparity 52.7 min and relative disparity 1.9 for the state average in waiting time). Likewise, significant associations between ITA and IPDSS were identified. In particular, we found association between all the proposed ITAs and the state rate of PCU, although with a weak effect index. Conclusions: Inequalities persist in the responsiveness during the provision of outpatient services to the population without social security. More work is needed to address inequalities and promote equity in health.